Redroot Pigweed (Amaranthus retroflexus L.) and Lamb’s Quarters (Chenopodium album L.) Populations Exhibit a High Degree of Morphological and Biochemical Diversity - Hamidzadeh Moghadam, Shiva; Alebrahim, Mohammad Taghi; Tobeh, Ahmad; Mohebodini, Mehdi; Werck-Reichhart, Danièle; MacGregor, Dana R.; Tseng, Te Ming (Frontiers in Plant Science, 2021)
Amaranthus retroflexus L. and Chenopodium album L. are noxious weeds that have a ‎cosmopolitan distribution. These species successfully invade and are adapted to a wide ‎variety of diverse climates. In this paper we evaluated the morphology and biochemistry of 16 ‎populations of A. retroflexus L. and 17 populations of C. album L.. Seeds from populations ‎collected from Spain, France and Iran were grown together at the experimental field of the ‎agriculture research of University of Mohaghegh Ardabili and a suite of morphological traits ‎and biochemical traits were assessed. Among the populations of A. retroflexus L. and of C. ‎album L. were observed significant differences for all the measured traits. The number of ‎branches for A. retroflexus L. (12.22) and inflorescence length (14.34) for C. album L. were ‎the two characteristics that exhibited the maximum coefficient of variation. Principal ‎component analysis of these data identified four principal components for each species that ‎‎explained 83.54 (A. retroflexus L.) and 88.98 (C. album L.) of the total variation. ‎A ‎dendrogram based on unweighted neighbor-joining method clustered all the A. retroflexus L. ‎and C. album L. into two main clusters and four sub-clusters. Canonical correlation analysis ‎was used to evaluate relationships between climate ‎classification of origin and traits. ‎Similarly, the measured characteristics did not group along Köppen climate classification. ‎Both analyses support the conclusion that A. retroflexus L. and C. album L. exhibit high levels ‎of diversity despite similar environmental histories. Both species also exhibit a high diversity ‎of the measured biochemical compounds indicating they exhibit different metabolic profiles ‎even when grown concurrently and sympatrically. Several of the biochemical constituents ‎identified in our study could serve as effective indices for indirect selection of stresses ‎resistance/tolerance of A. retroflexus L. and C. album L. The diversity of the morphological ‎and biochemical traits observed among these populations illustrates how the unique selection ‎pressures faced by each population can alter the biology of these plants. This understanding ‎provides new insights to how these invasive plant species successfully colonize diverse ‎ecosystems and suggests methods for their management under novel and changing ‎environmental conditions. ‎